Semantics of the Qur’anic Weltanschauung: a critical analysis of Toshihiko Izutsu’s works - Solihu, Abdul Kabir Hussain (Association of Muslim Social Scientists, 2009)
This paper examines the structural semantic approach based on the theory of linguistic relativity to scriptural language as exemplified in Toshihiko Izutsu’s studies of the Qur’anic weltanschauung. According to this theory, each language contains a particular worldview that causes its speakers to view the world in a way different from the speakers of other languages. By an analytical study of the semantic fields and contextual use of the Qur’an’s key conceptual terms, Izutsu explores the semantic factors believed to have been employed by the Qur’an in its Islamization of the jahili (pre-Islamic Arab) worldview. Such an approach exhibits that the Qur’an’s linguistic vision of reality is internally coherent but culturally and historically conditioned. Following a textual analysis, this study critically examines, from both an ethical and a theological perspective, the semantic theory that Izutsu applies to the Qur’an’s key concepts in his two works: God and Man in the Qur’an and Ethico-Religious Concepts in the Qur’an. The objective is to investigate the extent to which semantic analysis could enrich our understanding of the ontological problems raised in the Qur’an.